THE INFLUENCE OF INCOME LEVEL ON COMMUNITY CONSUMPTION LEVEL IN SOPPENG REGENCY (CASE STUDY IN CONGKO VILLAGE, MARIORIWAWO DISTRICT) - Achsanuddin UA, Anur; Adil, Muhammad (Jurnal Ekonomi Balance, 2020)
The purpose of this study is to meet the unlimited needs of life but the level of ability to meet their needs is limited to a problem that often occurs. This is influenced by the level. The purpose of this study was to determine the effect of income levels on the level of community consumption in Soppeng district (a case study in Congko village, Marioriwawo district). This researcher uses a quantitative analysis method which is an overview of the effect of income levels on the level of community consumption in Marioriwawo District, Soppeng Regency. The level of population consumption that is measured or generated through the results of partial test calculations with a value of tcount 10.808, this is very influential significantly and has a positive impact on the level of public consumption where t table is 1.988 where the significant value is 0.000 <0.05